The underlying mechanism behind the different outcomes of COVID-19 in children and adults - Shang, Zifang; Huang, Ling; Qin, Shijie (Frontiers in Immunology, 2025)
Coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, has affected hundreds of millions of people globally, resulting in millions of deaths. During this pandemic, children have demonstrated greater resistance than adults, exhibiting lower infection rates, reduced mortality, and milder symptoms. Summarizing the differences in resistance between children and adults during COVID-19 can provide insights into protective mechanisms and potential implications for future treatments. In this review, we focused on summarizing and discussing the mechanisms for better protection of children in COVID-19. These protective mechanisms encompass several factors: the baseline expression of cell surface receptor ACE2 and hydrolase TMPRSS2, the impact of complications on COVID-19, and age-related cytokine profiles. Additionally, differences in local and systemic immune responses between children and adults also contribute significantly, particularly interferon responses, heterologous protection from non-COVID-19 vaccinations, and immune status variations influenced by micronutrient levels. The advantageous protection mechanisms of these children may provide insights into the prevention and treatment of COVID-19. Importantly, while age-related metabolic profiles and differential COVID-19 vaccine responses may contribute to protection in children, current comparative research remains limited and requires further investigation.